The Effect of Conservation Use on Technical Efficiency of Carrot Farming in East Java, Indonesia - Imanullah, Muhammad Diffa; Asmara, Rosihan; Fahriyah, Fahriyah (Agro Bali : Agricultural Journal, 2025)
East Java Province, one of the carrot centers, experiences fluctuations in carrot production, which is thought to be due to inefficient production factors and land degradation due to low conservation use. The study investigates the level of conservation activities adopted by carrot farmers in East Java Province, focusing on technical efficiency and the impact of socio-economic factors on this efficiency. This study was conducted purposively in Sumberbrantas Village, Batu City, and Wonokerso Village, Probolinggo Regency, using a simple random sampling method with data collection through interviews. The analysis method used was the Likert scale scoring method for the level of conservation adoption by farmers, stochastic frontier analysis using the Cobb-Douglas function with maximum likelihood estimate (MLE), and tobit regression analysis to determine the effect of conservation on technical efficiency. Results show that conservation adoption is mostly low, with factors like land, chemical fertilizers, organic fertilizers, pesticides, and labor positively affecting production. The average level of technical efficiency is 0.4970, with location and education having a significant positive effect. Conservation variables do not have a significant effect.